The Diary of Heinrich Witt (10 vols.) - Mücke, Ulrich (Brill, 2015)
The diary of Heinrich Witt (1799-1892) is the most extensive private diary written in Latin America known to us today. Written in English by a German migrant who lived in Lima, it is a unique source for the history of Peru, and for international trade and migration. Readership: All interested in the history of Peru, of Altona and Hamburg and of international trade and migration in the 19th century, and anyone concerned with autobiographical writing at that time.